Pengaruh Media Pembelajaran Berbasis PowerPoint Hyperlink terhadap Kemampuan Berpikir Kritis Siswa - Yuyun Lesmana; Siti Umi Hani; Linda Dwi Nurmasyanti; Rijal Agustian; Iik Taopik Hasan (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This article aims to find out how the influence of the Power Point Hyperlink learning media on the critical thinking skills of students in the fifth-grade science subject at MI Miftahul Khoer. This research was conducted at MI Miftahul Khoer, Kumpay Village, Jalancagak. This research is quantitative research with a Quasy Experiment type of research. The population in this study were all students of MI Miftahul Khoer, amounting to 200. The sample of this study was 1 class with 32 students and divided into 2 groups consisting of an experimental group with 16 students and a control group with 16 students. person. The test instrument used to determine the critical thinking of students in science subjects is an essay test in the form of a post-test which consists of 10 questions. The data analysis technique used in this study used the ttest. Based on the research that has been carried out, it can be concluded that there is an influence of hyperlink power point learning media on the critical thinking skills of science subjects at MI Miftahul Khoer. This can be seen from the average value of critical thinking in science subjects, which is seen from the average post-test score in the experimental class is 81.25 and the post-test score in the control class is 66,725.